MATHEMATICAL MODELING OF CRITICAL PHENOMENA ACCORDING TО THE PLEBIANSKY-DEMYANSKY METRIC - Kazakov, Anatoly; Shapovlov, Hennady; Oleynyk, Vyacheslav (European Science, 2023)
Based on the generalization of the theory of Landau phase transitions and the provisions of Thom's theory of catastrophes, the fulfillment of the conditions of stability, singularity, and the emergence of phase coexistence spaces for the family of solut